Effect of Whatsapp Reminder on Antenatal Care Revisit Compliance and Knowledge of Pregnancy Danger Signs During the Covid-19 Pandemic - Maliha Amin; Elita Vasra; Intan Kumalasari; Maksuk; Faiza Yuniati; Sari Aisa (Universitas STRADA Indonesia, 2022)
ANC repeat visits experienced a significant decline during the pandemic due to maternal concerns about the transmission of the Covid-19 virus. The absence of the mother in the visit causes limited information in recognizing the danger signs of pregnancy. This can be anticipated with the WhatsApp Reminder service as a supporting intervention to increase maternal compliance and knowledge. This study aims to determine the effect of WhatsApp Reminder on ANC visit compliance and knowledge of pregnancy danger signs. This pre-experimental study used a one group pre-test post-test design for one group of subjects. Sampling using simple random sampling was 30 respondents in third trimester mothers at Puskesmas 5 Ilir Palembang in June 2021. Collecting data with the MMAS-8 instrument and analyzed using the Marginal Homogeneity test with a significant level of <0.05. The results showed a high level of compliance 60% and good knowledge 74% with p = 0.000.